The Correlation between Self-Concept and Motivation Towards Nursing Students’ Achievement During Covid-19 Pandemic - Edison Kabak; Nuriati Sarlota Auparai; Yoel Halitopo (Malahayati Nursing Journal, 2022)
ABSTRACT Education is one of the sectors hardest hit during the COVID-19 pandemic. The effect is not only on the application of online learnings due to social distancing restrictions. But also on changes in the level of motivation that affect their learning achievement. In the long term, the phenomena will harm the students, lecturers, campus management, and various other parties. The objective is to examine students' self-concept and learning motivation during the Covid-19 pandemic and test whether it has a correlation with academic achievement and provide a possible solution. The method was quantitative with a descriptive-analytic design and cross-sectional approach. The main data collected was from the evaluation of 5 subjects before and during the Covid-19 pandemic and the analysis of the questionnaire. The sampling technique was non-probability sampling with a sample of nursing students in semester V, 57 respondents. Both data were collected from December 2020 to February 2021 in Wamena, Papua. The data collection tool used a standard questionnaire by Fitts designed in a Likert scale, focusing on self-concept and motivation. Data were analyzed using the application software SPSS (Statistical Package for Social Sciences) Version 25. The results were 30 respondents (52.6%) with student self-concept in the positive category and 26 respondents (45.6%) students who had achievement motivation to study in the good category with p-value = 0.000 (0, 05) so that Ho is rejected, which means that there is a significant influence between self-concept on learning achievement motivation. Keywords: Self-Concept, Nursing Students, Learning Motivation